Effects of rapamycin and tacrolimus on mature endothelial cells and endothelial progenitor cells. - (:unkn) unknown (My University, 2012)
To investigate the effects of the potent immunosuppressive agents tacrolimus and rapamycin on the number of circulating mature endothelial cells and circulating endothelial progenitor cells in an experimental model. It was an experimental study performed from December 2007 to January 2008 in which the effects of the immunosuppressive agents tacrolimus and rapamycin on endothelial progenitr cells and circulating mature endothelial cells were analysed on 24 male wistar albino rats in a controlled environment model. Circulating cell populations were measured by flow-cytometric analysis. Maun-Whitney U test and analysis of vartiance were used for statistical purposes. Rapamycin increased the number of circulating mature endothelial cells approximately 2-fold compared to tacrolimus. The number of endothelial progenitor cells also was increased in the peripheral blood of rats treated with rapamycin compared to those treated with tacrolimus. The study showed that treatment with rapamycin is associated with an increase in endothelial progenitor cells and circulating mature endothelial cells. This increase may be associated with endothelial cell damage and repair.